Model for expression of personal entrepreneurship realization in the logistics sector - Drejeris, Rolandas; Mažukna, Mykolas (Edelweiss Applied Science and Technology, 2025)
The global logistics sector offers significant opportunities for entrepreneurial growth, yet aspiring entrepreneurs often face challenges due to a lack of structured guidance in business creation. This paper addresses this issue by developing a universally applicable business creation model designed to increase the likelihood of successful logistics business establishment. The model systematically guides entrepreneurs through key decision-making stages, including choosing a business model, legal form, location, and financing sources. The methodological section provides decision-making support by implementing a multi-criteria evaluation approach—specifically, the Simple Additive Weighting (SAW) method—combined with criteria derived from modern academic literature. During practical implementation, the proposed model helped identify 10 logistics business models and 9 key evaluation criteria. Results showed that the model can effectively incorporate diverse expert evaluations, enabling more objective and efficient decision-making when selecting viable business creation options. The model was also tested by an entrepreneur establishing a new logistics company; the company, successfully launched, has been operating for over 10 months. The practical application confirms that the proposed model is a useful and adaptable tool for new entrants in the logistics sector seeking structured guidance throughout the business creation process.